Elementary functions - Wooton, William; Drooyan, Irving (California : Wadsworth Publishing Company, 1971)
This book is designed for students who have completed the equivalent of one and one-half to two years of high school algebra and one year of hig school geometry but, nevertheless, need additional preparation before undertaking more advanced courses in mathematics.
1. Relations and functions -- 2. Graphs of equations and inequalities -- 3. Some properties of conic sections -- 4. Polynomial and rational functions -- 5. Exponential and logarithmic functions -- 6. Circular functions -- 7. Trigonometric functions -- 8. Inverse functions and conditional equations.
Includes index.
Keywords: ALGEBRA